Clinical Effect of Doxycycline Combined with Compound Sulfamethoxazole and Rifampicin in the Treatment of Brucellosis Spondylitis - Yang XM (Dove Medical Press, 2021)
Xin-Ming Yang, Yong-Li Jia, Ying Zhang, Pei-Nan Zhang, Yao Yao, Yan-Lin Yin, Ye Tian Department of Orthopaedics, The First Affiliated Hospital of Hebei North University, Zhangjiakou, 075000, Hebei, People’s Republic of ChinaCorrespondence: Xin-Ming YangDepartment of Orthopaedics, The First Affiliated Hospital of Hebei North University, No. 12, Changqing Road, Qiaoxi District, Zhangjiakou, 075000, Hebei, People’s Republic of ChinaTel +86 313-8046926Email yxm1120@sohu.comObjective: The purpose of this study was to determine the clinical value of triple antibiotic therapy consisting of doxycycline, compound sulfamethoxazole and rifampicin in the treatment of brucellosis spondylitis.Methods: A retrospective analysis was performed on 100 patients with brucellosis spondylitis admitted to the First Affiliated Hospital of Hebei North University from March 2016 to June 2019. Patients were divided into the following two groups: the control group (n = 50) treated with dual antibiotic therapy (rifampicin + compound sulfamethoxazole), and the observation group (n = 50) treated with triple antibiotic therapy (rifampicin + doxycycline + compound sulfamethoxazole). The treatment effect, low back pain relief, levels of erythrocyte sedimentation rate (ESR), procalcitonin (PCT) and C-reactive protein (CRP), as well as the adverse reactions were compared between the two groups.Results: The response rate of the observation group was significantly higher than that of the control group (P < 0.05). Before treatment, there was no significant difference in the low back pain assessed by the visual analogue scale (VAS), or levels of ESR, PCT and CRP between the two groups (P > 0.05). But after treatment, the VAS score and the levels of ESR, PCT and CRP in observation group were lower than those in the control group (P < 0.05). No significant difference was found in the incidence of adverse reactions (P > 0.05).Conclusion: The triple antibiotic therapy of doxycycline, compound sulfamethoxazole and rifampicin is effective in the treatment of brucellosis spondylitis. It can significantly alleviate patients’ back pain and inflammation with a high safety profile, which is worthy of clinical application.Keywords: doxycycline, compound sulfamethoxazole, rifampicin, Brucella, spondylitis